The Coin of Love and Virtue: Academic Libraries and Value in a Global Pandemic - Seale, Maura; Mirza, Rafia (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
In September 2010, the Association of College and Research Libraries released The Value of Academic Libraries: A Comprehensive Research Review and Report. The spread of the novel coronavirus and the resulting global pandemic has raised questions about the concept of value in academic libraries. How is value attributed? How does value function? What does it mean to demonstrate or prove our value? We begin with an overview and analysis of ACRL’s Value of Academic Libraries Initiative. We then provide a description and timeline of the spread of COVID-19 and the reaction of both institutions of higher education, academic libraries, professional library organizations, and individual librarians. The pandemic has created a new category of workers - “essential workers” - who provide vital services, perform maintenance work, and labor to keep infrastructures intact. The role of carework and careworkers in the pandemic helps illuminate the situation of academic librarians within regimes of neoliberal austerity. Ultimately we argue that although the discourse of library value seeks to prove library value rationally and empirically, through a lot of quantitative data, capitalism, the economy, and value are fundamentally irrational. Academic library value must be claimed politically; misrecognizing the nature of the problem and relying on commonsense understandings of value and the economic, which is what the discourse of library value has done for the past decade, goes nowhere.